2016
DOI: 10.5812/pedinfect.36953
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Respiratory Co-Infections in Children Less Than Five Years With Adenovirus Infection

Abstract: Background: Acute respiratory tract infection is associated with significant morbidity, mortality, and economic loss worldwide. Viral infections seem to be responsible for 80% of the cases. There are several reports on the influence of dual or multiple respiratory viral infections on the severity of disease in childhood. Objectives: A limited number of studies have been conducted on co-infection of Adenovirus (AdV) with coxsackievirus, human bocavirus (HBoV) and Mycoplasma pneumoniae (MP) in Iran. To address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The most common types were HAdV-B3, HAdV-C2, and HAdV-C1[ 13 ]. Former studies in Iran showed that 14.4% [ 14 ], 18.4% [ 3 ] and 35.5% [ 2 ] of children with SARI were positive for HAdV. In the latter study, the most prevalent species among children with SARI was HAdV-B (80.3%), followed by HAdV-C (15.5%), HAdV-D (2.8%) and HAdV-E (1.4%).…”
Section: Discussionmentioning
confidence: 92%
“…The most common types were HAdV-B3, HAdV-C2, and HAdV-C1[ 13 ]. Former studies in Iran showed that 14.4% [ 14 ], 18.4% [ 3 ] and 35.5% [ 2 ] of children with SARI were positive for HAdV. In the latter study, the most prevalent species among children with SARI was HAdV-B (80.3%), followed by HAdV-C (15.5%), HAdV-D (2.8%) and HAdV-E (1.4%).…”
Section: Discussionmentioning
confidence: 92%
“…The impact of MVI on severe viral respiratory disease remains uncertain [ [18] , [19] , [20] , [21] ]. Recent research even suggests that MVI may be protective against severe disease in some cases, unlike viral-bacterial infections, which most likely contribute to worse outcomes [ [20] , [21] , [22] ]. In this study, viral co-infection was not significantly associated to hospital admission or death.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the prevalence of HBoV varied from one country to another. The HBoV prevalence, in cases of respiratory tract infection in children, ranged from 0% in Iran to 56.8% in Egypt [16,30]. In adults, the highest prevalence (6.6%) was observed in Iran [27].…”
Section: Discussionmentioning
confidence: 99%